2015
DOI: 10.1177/2331216515617916
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Binaural Pre-processing Strategies I

Abstract: In a collaborative research project, several monaural and binaural noise reduction algorithms have been comprehensively evaluated. In this article, eight selected noise reduction algorithms were assessed using instrumental measures, with a focus on the instrumental evaluation of speech intelligibility. Four distinct, reverberant scenarios were created to reflect everyday listening situations: a stationary speech-shaped noise, a multitalker babble noise, a single interfering talker, and a realistic cafeteria no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 42 publications
2
53
1
Order By: Relevance
“…In this study, we examine performance using a beamforming microphone array that combines signals from 16 microphones mounted on a headband. The intelligibility-weighted directivity index of this array is around 9 dB, similar to values reported in the literature for other beamformers (e.g., Baumgärtel et al., 2015 ; Desloge et al., 1997 ; Kates & Weiss, 1996 ; Soede, Bilsen, & Berkhout, 1993 ; Stadler & Rabinowitz, 1993 ). Previous studies from our laboratory have demonstrated that this type of beamformer can enhance speech intelligibility (relative to natural binaural listening) for fixed-location, frontal speech targets amidst spatially separated maskers ( Kidd, 2017 ; Kidd, Favrot, Desloge, Streeter, & Mason, 2013 ; Kidd, Mason, Best, & Swaminathan, 2015 ).…”
Section: Introductionsupporting
confidence: 86%
“…In this study, we examine performance using a beamforming microphone array that combines signals from 16 microphones mounted on a headband. The intelligibility-weighted directivity index of this array is around 9 dB, similar to values reported in the literature for other beamformers (e.g., Baumgärtel et al., 2015 ; Desloge et al., 1997 ; Kates & Weiss, 1996 ; Soede, Bilsen, & Berkhout, 1993 ; Stadler & Rabinowitz, 1993 ). Previous studies from our laboratory have demonstrated that this type of beamformer can enhance speech intelligibility (relative to natural binaural listening) for fixed-location, frontal speech targets amidst spatially separated maskers ( Kidd, 2017 ; Kidd, Favrot, Desloge, Streeter, & Mason, 2013 ; Kidd, Mason, Best, & Swaminathan, 2015 ).…”
Section: Introductionsupporting
confidence: 86%
“…To achieve binaural noise reduction with binaural cue preservation, two main concepts have been developed. In the first concept, a common real-valued spectro-temporal gain is applied to the reference microphone signals in the left and the right hearing device [4][5][6][7][8][9][10], ensuring perfect preservation of the instantaneous binaural cues but inevitably introducing speech distortion. The second concept, which is considered in this paper, is to apply a complex-valued filter to all available microphone signals on the left and the right hearing device using binaural extensions of spatial filtering techniques [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms have been described and instrumentally evaluated in depth in an accompanying study ( Baumgärtel et al., 2015 ). In a second accompanying article ( Völker, Warzybok, & Ernst, 2015 ), the same algorithms were tested in the same noise scenarios with acoustically stimulated hearing-impaired (HI) and normal-hearing (NH) listeners.…”
Section: Introductionmentioning
confidence: 99%